Improved strategies for calculating annual averages of ambient air pollutants in cases of incomplete data coverage - Brown, Richard J. C; Harris, Peter M; Cox, Maurice G (Environmental science--processes & impacts, 2013)
The consequences of missing data during air quality monitoring activities and the calculation of the annual average mass concentration of ambient pollutants are discussed. Possible strategies for mitigating totally and partially missing data during given measurement periods are presented and evaluated. A mathematical description of a preferred method for the determination of annual average concentration using the simple mean, and not using time weighting to account for missing data, is justified. It is hoped this discussion paper will provoke debate in the air quality community about the best way to assess measured concentrations of ambient pollutants against legislative values. The benefits of improved strategies for calculating annual averages of ambient air pollutants in cases of incomplete data coverage are discussed.